first solve each equation for y
![\begin{gathered} 2x-9y=-5 \\ -9y=-5-2x \\ y=(5)/(9)+(2)/(9)x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/x779utjy942tch7yhmzl7mgbpyae79gnc0.png)
![\begin{gathered} 4x-y=2 \\ -y=2-4x \\ y=-2+4x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/mq7jv8iduk9id9didykkbdoiwi1r0m5a4k.png)
the equations are
![\begin{gathered} y=(5)/(9)+(2)/(9)x \\ \\ y=-2+4x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/43vfzrefk6m9rsr2kdp5splvd6t732q0nj.png)
we can substract the equations to remove y
![\begin{gathered} y=(5)/(9)+(2)/(9)x \\ \\ y=-2+4x \\ \\ ---------------- \\ 0=(23)/(9)-(34)/(9)x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/dkzkfvb0akaocozxdby2x4pp7h8lajw3jl.png)
now solve x
![\begin{gathered} (23)/(9)-(34)/(9)x=0 \\ \\ 23-34x=0 \\ 34x=23 \\ \\ x=(23)/(34) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/jvr526mdwm1zl7hkvpkj3ca4ub7cwx1efl.png)
the value of x is 23/34, now replace on any equation to find Y, I will replace on the second
![\begin{gathered} y=-2+4((23)/(34)) \\ \\ y=-2+(46)/(17) \\ \\ y=(12)/(17) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/g5otr8rh8006ljxud7xjz2kzhuqgrt0imj.png)
the value of y is 12/17
the solution point is ( 23/34 , 12/17)